1988
DOI: 10.3171/jns.1988.68.3.0393
|View full text |Cite
|
Sign up to set email alerts
|

Dose-escalation study of intravenous nicardipine in patients with aneurysmal subarachnoid hemorrhage

Abstract: A dose-escalation study of the calcium ion entry blocking drug nicardipine was performed using large dose infusions in 67 patients with recent aneurysmal subarachnoid hemorrhage (SAH). A safe, potentially therapeutic dose of the drug was determined. Patients admitted within 7 days of SAH from a documented cerebral aneurysm were entered into the study if no spasm was present on the initial angiogram. Nicardipine was administered as a continuous intravenous infusion throughout the 14-day period after SAH, regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…The details of this study are described elsewhere. 7 In all cases, blood in the subarachnoid space was evident on either computed tomography (CT) or nontraumatic lumbar puncture. Cerebral angiography to demonstrate the presence of a saccular aneurysm and the absence of vasospasm was performed before patients were entered into the study.…”
Section: Methodsmentioning
confidence: 94%
“…The details of this study are described elsewhere. 7 In all cases, blood in the subarachnoid space was evident on either computed tomography (CT) or nontraumatic lumbar puncture. Cerebral angiography to demonstrate the presence of a saccular aneurysm and the absence of vasospasm was performed before patients were entered into the study.…”
Section: Methodsmentioning
confidence: 94%
“…Studies demonstrated that nicardipine, a Ca 2+ -channel blocker, could improve the impaired cerebral circulation (33,34). The ocular vasculature anatomically and functionally resembles the cerebral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the marked degradation of contractile and cytoskeletal proteins also contributes to the development of vasospasm, and this probably occurs by severe uncoupling of the contractile units from the cytoskeleton. Flamm, et al, 18 reported that the intravenous infusion of high doses of nicardipine had significantly beneficial effects on development of delayed cerebral ischemia after aneurysmal SAH. In our clinic similar results have been reported in early treatment with high doses of nicardipine as early as possible within 24 hours after SAH, 44 suggesting that the therapeutic reduction of intracellular Ca ++ is an important measure to prevent development of vasospasm.…”
Section: The Continuous Increase In Intracellular Camentioning
confidence: 99%